Environments for Child Development The Case of Israel - Kravetz, Nathan ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
Child development in Israel takes place in a context of many unique influences. Influences which define the nature of family experience include religion, ethnic group membership, immigrant or non-immigrant status, and urban or rural living. All of these influences are situated within, and further influenced by, the continuous state of military threat and need for defense vigilance. The ideology which formed the state, Zionism, is blended necessarily with the religious precepts of Judaism. These precepts, in surrounding the child with "givens," vary in their effects depending on their value to the child's milieu and to his or her own developing adherences. Most Israeli children live in the urban milieu, where privacy is at a premium and where there is a minimum of planned experience. Though the kibbutzniks comprise only 4% of the population, their environment is so determined, controlled, and ultimately effective that the impact on the nation is much greater than their actual numbers would suggest. For the Arab child in Israel there is a potential for development within a set of environments, the traditional and the innovative. The homes and communities of the Arab children, though essentially rural and religion-bound, differ from those of children in other Arab countries. (Author/SS)
ERIC Note: Paper originally presented in briefer form at the Western Regional Conference of the Comparative and International Education Society (Tempe, AZ, October 11-13, 1979).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Arabs; Child Development; Cross Cultural Studies; Cultural Context; Cultural Influences; Ethnic Groups; Family Environment; Jews; Religious Cultural Groups; Religious Factors; Israel; Kibbutzim; Opinion Papers